In vitro bleaching efficacy of violet LED associated with 10% hydrogen peroxide and 10% carbamide peroxide - Leite, Juliana Squizatto; Gonçalves, Cristiane Orizio; Hortkoff, Diego Rafael de Andrade; Gomes, Giovana Mongruel; Rastelli, Alessandra Nara de Souza [UNESP]; Gomes, João Carlos (Elsevier, 2023)
Background: This in vitro study evaluated the efficacy and the effect over the dental enamel surface of violet LED dental bleaching associated to different concentrations of carbamide and hydrogen peroxide. Methods: Human dental blocks (n = 100) were randomly distributed into 5 groups: 10% hydrogen peroxide (HP10), 10% carbamide peroxide (CP10), 10% hydrogen peroxide with violet LED (VHP10), 10% carbamide peroxide with violet LED (VCP10) and 35% hydrogen peroxide (HP35). The specimens were analyzed by Vickers microhardness test (n = 50) initially, immediately after and seven days after ending the bleaching protocol. For color analysis (n = 50), the specimens were evaluated for bleaching effectiveness (ΔE2000, ΔE1976) and whiteness index (ΔWID) with EasyShade spectrophotometer, before bleaching protocol and seven days after ending the bleaching protocol. The microhardness and color data were analyzed using one-way ANOVA with post-hoc Tukey test (α = 0.05). Results: The microhardness values showed difference among the investigated groups only immediately after the end of the dental bleaching (p < 0.05), with reduction for the groups HP35 (p < 0.01) and HP10 (p < 0.05), however the microhardness values were reestablished after seven days. Regarding the color changes, a difference between VHP10 and the others groups evaluated for ΔE2000 and ΔE1976 index was observed (p < 0.05). For ΔWID, there was no difference between the studied groups. Conclusions: Violet LED associated with low concentration bleaching agents did not show a negative effect on dental enamel regarding the surface microhardness. All bleaching protocols were effective, therefore, perceptible to human eyes.
Keywords: Bleaching agents; Dental bleaching; Light; violet LED